CAD Technology Workshop with the Pierre Bougher Approach in Building Traditional Wooden Ships at Kelompok Usaha Bersama (KUB) Nenang Berlayar North Penajam Paser - Hariyono, Hariyono; Ikhwani, Rodlian Jamal; Sitorus, Chris Jeremy Verian; Kustiwansa, Harlian (Naval Architecture Department, Kalimantan Institut of Technology, 2024)
Program in the form of a CAD Technology Workshop using the Pierre Bouguer approach aims to improve the skills of traditional wooden ship craftsmen in the Kelompok Usaha Bersama (KUB) Nenang Berlayar, Penajam Paser Utara. This activity introduces Computer-Aided Design (CAD) technology as a modern solution to increase the precision, efficiency and quality of wooden ship designs without eliminating traditional values. Pierre Bouguer's approach which focuses on the stability and balance of the ship through drawing lines plans was applied to produce a better design from a technical and safety perspective. Implementation methods include intensive training, technical assistance, and ongoing evaluation, supported by lecturers and students from the Kalimantan Institute of Technology (ITK). The results of the activity showed a significant increase in craftsmen's understanding and ability to use CAD, as seen from the post-test results of participants who achieved an application level above 90%. This program not only helps craftsmen adopt modern technology but also creates a sustainable learning ecosystem through an online-based community. It is hoped that the application of CAD technology can encourage innovation in traditional wooden shipbuilding, increase competitiveness, and provide added economic value for craftsmen amidst the challenges of modernizing the maritime industry.